IMPLEMENTASI FUNGSI PENGAWASAN DPRD DALAM MEWUJUDKAN PENYELENGGARAAN PEMERINTAHAN KABUPATEN YAHUKIMO - Inuk, Atius; Sapioper, Hiskia C.M.; Ohoiwutun, Yosephina (JURNAL KEBIJAKAN PUBLIK, 2025)
This study aims to analyze the implementation of the supervisory function of the Regional People's Representative Council (DPRD) in the government of Yahukimo Regency, as well as the supporting and inhibiting factors. The urgency of this research lies in the importance of strengthening the supervisory function of the Regional Representative Council so that accountability and transparency in regional administration can be better guaranteed. This study uses a qualitative research method with a descriptive approach. The data collection techniques used are interviews, observation, literature study, and documentation. Informants are selected purposively. Data analysis includes the stages of data reduction, data presentation, and drawing conclusions and verification. The implementation of the supervisory function of the DPRD in Yahukimo Regency is analyzed using Edwards III's theoretical framework, which includes communication, resources, disposition, and bureaucratic structure. The results of the study indicate that internal communication within the DPRD is well established, but obstacles arise when dealing with local governments that lack transparency, thereby slowing down access to information and reducing the effectiveness of oversight. In terms of resources, the limited number of members and supporting facilities, as well as the lack of budget, pose challenges in overseeing a vast area. Although the DPRD demonstrates a positive disposition and high commitment in performing its duties, the lack of support and budget from the local government often hinders the continuity of oversight. In terms of bureaucratic structure, clear task distribution and the use of standard operating procedures (SOPs) enhance oversight efficiency. Supporting factors, such as the competence of DPRD members and community participation, play a crucial role in oversight effectiveness. However, these are hindered by limitations in human resources, budget constraints, lack of transparency, weak coordination, and political interests that undermine the objectivity of oversight.